Julia Kristeva Intertextual of Feminism in the Film Pangku by Reza Rahardian - Agung Drajat (LPPAIK Universitas Muhammadiyah Bandung, 2026)
Reza Rahadian's film Pangku represents the lives of women who are under social, economic and patriarchal cultural pressure. Through the main character, Sartika, this film shows how women must face various life constraints while fulfilling their roles as mothers and breadwinners. This study analyzes the film